Tinggalan Megalitik dan Kubur Tempayan Dataran Tinggi Jambi - Tri Marhaeni S. Budisantosa; Sigit Eko Prasetyo (Badan Riset dan Inovasi Nasional, 2022)
The highlands of Jambi is one of the region of the distribution of Megalithic and urn cemetery culture, then it can be regarded as an archaeological culture area in pre-Islamic. In the region has been found twentyone Megalithics in cylindrical or conical form, and one round shaped. In addition it has also found six urn cemeteries complexes which proved to be associated with Megalithics. Megalithic and urn cemetery in the highlands of Jambi has become the object of research for Archeological Research Center and Development in collaboration with foreign researchers and conducted by the Archeological Research Center and Development and Archaeological Center of Palembang themselves. Archaeological Center of Palembang each year doing research since 2006 with the aim to reveal aspects of past human life such as economy, social, and religious in the local and regional context. The data obtained so far have achieved that goal, although the conclusions can be debated.